Evaluasi Tingkat Keberhasilan Program Desa Wisata Nongkosawit Kecamatan Gunungpati di Kota Semarang - Deanira Chikita Edelweis; Agung Sugiri (Jurusan Perencanaan Wilayah dan Kota, 2018)
Tourism activities recently becoming a necessity and a lifestyle of most societies. One of the tourism that is growing quite rapidly is a tourism based on rural areas. The village becomes one of potential resources and has good prospects to develop as it has strong potential to attract tourists, especially for tourists coming from urban areas. Rural-based tourism also plays a role in improving the economy and improving the welfare of the community in the location itself by using the concept of Community Based Tourism (CBT), where local communities also play an active role in the development.Semarang City is one part of the program